Phages in Treatment of Some Deep Purulent Skin Infections - Kiladze N.; Chanishvili N.; Shulaia T.; Bendeliani Z.; Zaichenko Y. (Львівський клінічний вісник)
Introduction. The questions of treatment of chronic skin purulent infections are extremely important due to their wide spread, severe clinical course of some nosological forms, development of resistance to the traditional means, and growth of undesirable side effects of antibiotic therapy. Chronic suppurative skin diseases connected with skin appendages are disorders of common occurrence and a major constituent of pyodermas. They still remain a problem due to their chronic character and difficulty of treatment, as well as its large impact on patients’ quality of life. Due to the chronic course of the disease, treatment is long lasting, and often ineffective because of resistance to antibiotics therefore it is desirable to provide the treatment with effective alternatives to commonly used antibiotics to reduce the resistance and obtain a highly specific agent which is able to destroy bacteria effectively. In the same time across the world a growing number of scientists are noting the promising positive results of phage therapy and its advantages, especially in the treatment of chronic cases. The aim of this communication, which is a continuation of previously presented research, is to report the data and results of treatment of some common chronic suppurative skin disease with phages. Materials and methods. In the present investigation were included 87 males aged 18 to 56 with chronic folliculites (n=52), syccosis (n=30) and folliculitis et perifolliculitis capitis abscendens et suffodiens, Hoffmann (n=5), in all cases was approved prevalence of staphylococcal flora and all of them were treated before with antibiotics, but unsuccessfully. The treatment was provided with pyophages produced by Giorgi Eliava Institute (Tbilisi, Georgia) which include Staphylococcus aureus, Streptococcus (different cultures), Escherichia coli (different serotypes), Psedomonas aeruginosa, Proteus vulgaris, mirabilis. Taking into consideration deep locations for treatment was chosen mesotherapy technique – phage solution was injected by dermal nappage, papula and point by point technique in all damaged areas. In each case the frequency of procedures was usually once in 3-4 days until healing, the process took about one month. In patients with folliculitis full recovery was achieved in all cases, but they were still under observation up to 2 months in order to avoid relapses. In the cases of folliculitis et perifolliculitis capitis abscendens et suffodiens Hoffmann treatment was started with М. Jessner’s peeling followed by intralesional injections into buggy nodules and sinus tracts and dermal nappage, papula and point by point technique in all damaged areas. Patients were treated within three weeks once in three days with following break of 7 days, after the course was repeated. In all 5 cases the final results were positive. The cosmetic defect in the form of a fibroid growth was still present, but after the course of treatment the laboratory data confirmed the absence of pathogenic flora in correlation with marked clinical improvement. Conclusions. Рhage therapy has a long history and phages potential for treating infectious diseases has been pursued since their discovery, but still there are many important questions that must be decided before their wide therapeutic use in different clinical fields. Their benefits are undeniable, this therapy may replace or augment the conventional antibiotic therapy, help eliminate antibiotic resistance of bacterial strains and they give a real chance for patients suffering from chronic infections caused by antibiotic-resistant bacteria. The experience in phage therapy may become very important with the rapidly-increasing spread of antibiotic-resistance bacterial infections which are difficult to treat now. There is a need to develop phage therapy of purulent skin diseases, but more research is needed to understand the bacteria-bacteriophage interactions in the skin community to obtain comprehensive knowledge on different pathogenic flora.